Association of nutritional support programs with zinc deficiency in Colombian children: a cross-sectional study (2019)
Background: Zinc is an essential trace element that plays a key role in the immune, gastrointestinal, respiratory and nervous systems. In Colombia, a vast percentage of children live in low-income households with food insecurity and nutritional deficiencies, including zinc. In an effort to improve children's well-being, public health measures such as nutritional support programs that provide meals have targeted the poorest populations. The aim of the present study was to assess the role of nutritional support programs on zinc deficiency in Colombian children, while considering their wealth and food security.Methods: Cross-sectional study using data from the 2010 Colombian National Nutrition Survey, a population-based study representative of Colombia. A total of 4275 children between 12 and 59months of age were included in the study. Stepwise logistic regressions were modelled with SPSS, first for zinc deficiency on wealth and food security, then adding enrolment in a nutritional support program, and finally, adjusting for socio-demographic variables.Results: A zinc deficiency prevalence of 49% was found. The adjusted models showed an association of wealth quintiles: very poor (OR=1.48) and poor (OR=1.39), food security (OR=0.75) and enrolment in a nutritional support program (OR=0.76) with zinc deficiency. Enrolment in nutritional programs did not modify the relationship of wealth and food security to zinc deficiency.Conclusion: Zinc deficiency is associated with wealth, food security and enrolment in nutritional support programs. Nutritional programs may be a good alternative against zinc deficiency, if they focus appropriately on the needs of children according to their wealth and food security.